The effects of Indonesia's ‘Midwife in the Village’ programme 10 years post-launch - Triyana, Margaret (2016)
Data from the Indonesian Family Life Survey (1993–2000) were used to examine whether the effects of the Indonesian ‘Midwife in the Village’ programme persisted more than 10 years after its implementation. The study followed up earlier studies of the programme’s effects by estimating its effects on pregnancy outcomes, using propensity-score matching applied to data collected after the 1997 Asian economic crisis. The results indicate that only the programme’s effect on the use of prenatal care services persisted, and that the loss of village midwives during the crisis had no significant effect on pregnancy outcomes.